Molecular Diagnosis of Nitrate Reducing Bacteria In Healthy Oral Cavities - Athraa K. Jawad; Nawar Al-Janabi (JOURNAL OF MEDICAL AND HEALTH SCIENCE, 2026)
Background: The oral cavity harbors a highly diverse microbial community, within which nitrate-reducing bacteria (NRB) constitute a functional core group contributing to microbial balance and systemic health through nitric oxide (NO) production. Objectives: The present study aimed to detect and characterize NRB from the oral cavities of healthy individuals using a selective molecular approach. Methods: A total of ten oral samples were collected and cultured on Brain Heart Infusion (BHI) agar prior to DNA extraction. A species-specific primer targeting Rothia mucilaginosa, a well-documented oral NRB, was designed and applied in PCR assays. Results: The analysis revealed the presence of Rothia mucilaginosa in one positive sample (10%). Although the prevalence was limited compared to previous studies reporting broader NRB diversity, the detection of Rothia mucilaginosa underscores its ecological relevance in nitrate reduction within the oral environment. Conclusion: Collectively, these findings demonstrated the feasibility of selective molecular detection, highlight Rothia mucilaginosa as a potential biomarker for oral and systemic health, and emphasize the need to expand primer panels in future research to capture the full diversity of oral nitrate-reducing bacteria.